2005
DOI: 10.1088/0953-8984/17/31/026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peptides and ions interacting with an electrically neutral membrane interface on the structure and stability of lipid membranes in the liquid-crystalline phase and in the liquid-ordered phase

Abstract: We investigated the effects of a de novo designed peptide, WLFLLKKK (peptide-1) and La3+, which can bind with the electrically neutral lipid membrane interface, on the stability of the phosphatidylcholine (PC) membrane in the Lα phase and that of the liquid-ordered (lo) phase membranes. The results of spacing of the multilamellar vesicle and shape changes of the giant unilamellar vesicle (GUV) indicate that the peptide-1 can be partitioned into the membrane interface in the Lα phase but not into that in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Ions are known to affect membrane fusion and phase transitions (43,44). Divalent ions have also been demonstrated to change the bulk modulus of DPPC bilayers (45).…”
Section: Membrane Mechanicsmentioning
confidence: 99%
“…Ions are known to affect membrane fusion and phase transitions (43,44). Divalent ions have also been demonstrated to change the bulk modulus of DPPC bilayers (45).…”
Section: Membrane Mechanicsmentioning
confidence: 99%
“…These include membrane fluidity, bilayer thickness, hydration state of lipid headgroups, and interfacial polarity and charge . A change in pH or ion concentrations may result in a different lipid packing or, by a changed hydration, in an altered effective geometrical shape of the lipids. The equilibrium area per molecule at the surface is thus not a simple geometrical area but an equilibrium parameter derived from thermodynamic considerations, and it can have different values depending on temperature, salt concentrations, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The geometrical shape of the lipids also can cause spontaneous curvature of the membrane. This spontaneous curvature can furthermore change with varying pH or ion concentrations such that a difference in pH value or ion concentration between the inner and outer environments of the vesicle can cause a change in the vesicle shape. For example, Sano et al found that giant unilamellar vesicles (GUVs) of dipalmitoylphosphatidylcholine/cholesterol membranes undergo shape changes when La 3+ ions are added to the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%